2018
DOI: 10.1007/s00270-018-2120-z
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Irreversible Electroporation (IRE) of Hepatic Malignancy: A Bi-institutional Analysis of Safety and Outcomes

Abstract: Aim Irreversible electroporation (IRE) is a non-thermal ablative option in patients unsuitable for standard thermal ablation, due to its potential to preserve collagenous structures (vessels and ducts) and a reduced susceptibility to heat sink effects. In this series from two large tertiary referral hepatobiliary centres, we aim to assess the safety/outcomes of hepatic IRE. Materials and Methods Bi-institutional retrospective, longitudinal follow-up series of IRE for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 28 publications
3
26
0
1
Order By: Relevance
“…IRE, though, is executed percutaneously in many cancer centers, with the aid of image guidance. 34 Due to similar technological approach, electrochemotherapy can also be performed percutaneously. Same principles must be followed -careful pre-treatment planning, image guided electrode insertion and safe delivery of electric pulses with ECG synchronization.…”
Section: Discussionmentioning
confidence: 99%
“…IRE, though, is executed percutaneously in many cancer centers, with the aid of image guidance. 34 Due to similar technological approach, electrochemotherapy can also be performed percutaneously. Same principles must be followed -careful pre-treatment planning, image guided electrode insertion and safe delivery of electric pulses with ECG synchronization.…”
Section: Discussionmentioning
confidence: 99%
“…53 A more recent study of IRE for hepatic tumors which were "deemed unsuitable for thermal ablation" had a similar small cohort of 3 IHC out of 59 primary and metastatic liver tumors and IHC was not included in the tumor type grouping data used to compare outcomes. 54 The nonthermal technology offered by IRE may be advantageous in treating primary and recurrent IHC in patients where the tumor is located adjacent to sensitive structures.…”
Section: Irreversible Electroporation Of Intrahepatic Cholangiocarcinomamentioning
confidence: 99%
“…The survival of patients was reported to be 90% (95% CI 72-97%), 65% (95% CI 40-81%), 52% (95% CI 22-75%) at 12, 24 and 36 months respectively. The median time of progression was found to be eight months but was significantly faster in the colorectal cancer metastatic group than the HCC group [11]. Cheung et al studied the efficacy of IRE in 11 patients with 18 HCC tumors.…”
Section: Reviewmentioning
confidence: 99%
“…This was in contrast to other studies. Niessen et al and Mafeld et al demonstrated complete ablation in 92.2% and 75% of the tumors at six weeks and four to eight weeks of follow-up respectively [8,11]. Zeng et al compared IRE efficacy in large and medium-size liver tumors.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation